2016
DOI: 10.1186/s12984-016-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting learned non-use in chronic stroke patients with reinforcement-induced movement therapy

Abstract: BackgroundAfter stroke, patients who suffer from hemiparesis tend to suppress the use of the affected extremity, a condition called learned non-use. Consequently, the lack of training may lead to the progressive deterioration of motor function. Although Constraint-Induced Movement Therapies (CIMT) have shown to be effective in treating this condition, the method presents several limitations, and the high intensity of its protocols severely compromises its adherence. We propose a novel rehabilitation approach c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 56 publications
2
86
0
7
Order By: Relevance
“…Although shaping appears to be one of the essential components of CIMT, its particular effect on motor recovery has not been studied on its own (Kwakkel et al, 2015). Increasing difficulty has been successfully used in standard care studies (Woldag et al, 2010), robot-assisted therapy (Lucca, 2009), and VR-based systems (Cameirão et al, 2012;Ballester Rubio et al, 2016), all of which showed beneficial effects on motor recovery. Task difficulty appears to be implicitly present in many tasks that investigate motor learning without being explicitly operationalized.…”
Section: Increasing Difficultymentioning
confidence: 99%
“…Although shaping appears to be one of the essential components of CIMT, its particular effect on motor recovery has not been studied on its own (Kwakkel et al, 2015). Increasing difficulty has been successfully used in standard care studies (Woldag et al, 2010), robot-assisted therapy (Lucca, 2009), and VR-based systems (Cameirão et al, 2012;Ballester Rubio et al, 2016), all of which showed beneficial effects on motor recovery. Task difficulty appears to be implicitly present in many tasks that investigate motor learning without being explicitly operationalized.…”
Section: Increasing Difficultymentioning
confidence: 99%
“…This work builds on previous research conducted with the RGS, a VR-based tool that promotes functional recovery post-stroke through goal-oriented embodied sensorimotor stimulation. A number of studies suggest the effectivity of RGS protocols for overcoming upper limb motor deficits (Cameirão et al, 2012 da Silva Cameirão et al, 2011; Ballester et al, 2016, 2015, 2017). These protocols rest on principles that are derived from the Distributed Adaptive Control theory of mind and brain (Verschure, 2012), which places recovery in the context of the acquisition and expression of goal-oriented voluntary behavior driven by perception, memory, value and goals and the optimization of perceptual and behavioral prediction.…”
Section: Methodsmentioning
confidence: 99%
“…Verstärkte Rückmeldung durch virtuelle Realitäten (um eine erhöhte Genauigkeit und den Bewegungsumfang zielgerichteter Bewegungen zu reflektieren) führte in einer anderen Studie bei chronisch von Schlaganfall betroffenen Patienten zu einem Anstieg motorischer Leistungen (Fugl-Meyer Assessment of the Upper Extremity). Ebenfalls verbesserte sich so der Armgebrauch im Vergleich zu einer Kontrollgruppe ohne diese erfolgsorientierte Rückmeldung [1].…”
Section: Erhöhte Leistungserwartungunclassified